If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 9q + -2 = -2 Reorder the terms: -2 + 9q = -2 Add '2' to each side of the equation. -2 + 2 + 9q = -2 + 2 Combine like terms: -2 + 2 = 0 0 + 9q = -2 + 2 9q = -2 + 2 Combine like terms: -2 + 2 = 0 9q = 0 Solving 9q = 0 Solving for variable 'q'. Move all terms containing q to the left, all other terms to the right. Divide each side by '9'. q = 0 Simplifying q = 0
| 9x+8=89x | | 56=8z | | logk=20 | | 35=7s | | 0.5x=12x | | 24=3v | | 2+8m=18m | | 18=9c | | 8n+50=109 | | 24=2B+g | | (0,3/0,01)*2*((0,2*1,9*10^3)/(N*0,3*0,9))^(1/3)*(12/6)^(0,14) | | 4a^2-20a-24=0 | | 3x+5y+2z=2 | | -p^2+p+20=0 | | 4e=24 | | -3p-(-3)/-6=-12 | | 36=9m | | 7x-11/5x-2=2x-9/5x-2 | | 2x=9-5x+32 | | t+8=4t+5 | | 8z-6=7z | | ((x^2-ax-8)/(x-a))=0 | | 8(x-8)=4(x+4) | | (3x-4)(2x+5)=20 | | N^(2/3)=12,5 | | 2x+46=320 | | 5x+6+4x=-3(x-8)+7x | | (3.0075-6.0215)+t=2.105 | | x^3-x^2+2x-1=0 | | -5x+3=-6-2x | | 11(v+1)-3v=4(2v+4)-25 | | 3x-7x=-8 |